Influencing the audience through vector illustration in stop smuggling exotic animals campaign / Arifhakim Romly and Ahmad Sofiyuddin Mohd Shuib - Arifhakim, Romly; Ahmad Sofiyuddin, Mohd Shuib (Universiti Teknologi MARA, Perak, 2018)
This research aims to discuss how the vector illustration can create influence in educating our adult and young generation in Malaysia Peninsular about the exotic animals smuggling can caused extinction through Campaign and Illustration. The focus will be on producing characters design, below the line and above the line based from the type of illustration that the most audience decided to be most suitable. The implication from the finding in this study will help them to understand the situation of these animal and will help to preserve the exotic animals. The most important is that this finding will contribute to the graphic designer who working to convey messages to the society or target audience through illustration, can take this into consideration in achieving the good result in presenting to the society.